Endemism in the moss flora of North America. Issue 4 (7th April 2016) - Carter, Benjamin E.; Shaw, Blanka; Shaw, A. Jonathan
Abstract : PREMISE OF THE STUDY: Identifying regions of high endemism is a critical step toward understanding the mechanisms underlying diversification and establishing conservation priorities. Here, we identified regions of high moss endemism across North America. We also identified lineages that contribute disproportionately to endemism and document the progress of efforts to inventory the endemic flora. METHODS: To understand the documentation of endemic moss diversity in North America, we tabulated species publication dates to document the progress of species discovery across the continent. We analyzed herbarium specimen data and distribution data from the Flora of North America project to delineate major regions of moss endemism. Finally, we surveyed the literature to assess the importance of intercontinental vs. within‐continent diversification for generating endemic species. KEY RESULTS: Three primary regions of endemism were identified and two of these were further divided into a total of nine subregions. Overall endemic richness has two peaks, one in northern California and the Pacific Northwest, and the other in the southern Appalachians. Description of new endemic species has risen steeply over the last few decades, especially in western North America. Among the few studies documenting sister species relationships of endemics, recent diversification appears to have played a larger role in western North America, than in the east. CONCLUSIONS: Our understanding of bryophyte endemism continues to grow rapidly. Large continent‐wide data sets confirm early views on hotspots of endemic bryophyte richness and indicate a high rate of ongoing species discovery in North America.